Plant endemism in the Sierras of Córdoba and San Luis (Argentina): understanding links between phylogeny and regional biogeographical patterns - Chiapella, Jorge Oscar (2015)
We compiled a checklist with all known endemic plants occurring in the Sierras of Córdoba and San Luis, an isolated mountainous range located in central Argentina. In order to obtain a better understanding of the evolutionary history, relationships and age of the regional flora, we gathered basic information on the biogeographical and floristic affinities of the endemics, and documented the inclusion of each taxon in molecular phylogenies. We listed 89 taxa (including 69 species and 20 infraspecific taxa) belonging to 53 genera and 29 families. The endemics are not distributed evenly, being more abundant in the lower than in the middle and upper vegetation belts. Thirty-two genera (60.3%) have been included in phylogenetic analyses, but only ten (18.8%) included local endemic taxa. A total of 28 endemic taxa of the Sierras CSL have a clear relationship with a widespread species of the same genus, or with one found close to the area. Available phylogenies for some taxa show divergence times between 7.0 ? 1.8 Ma; all endemic taxa are most probably neoendemics sensu Stebbins and Major. Our analysis was specifically aimed at a particular geographic area, but the approach of analyzing phylogenetic patterns together with floristic or biogeographical relationships of the endemic taxa of an area, delimited by clear geomorphological features, could reveal evolutionary trends shaping the area.